(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This study investigates the role of servant leadership in promoting ethical behavior in organizations, by comparing its impact between nonprofit and commercial organizations. Through a systematic literature review approach using the PRISMA method, this research concludes that servant leadership positively influences work culture, organizational performance, and relationships with stakeholders. Implementing servant leadership can help build an inclusive organizational culture, increase employee engagement, and reduce unethical behavior.